Influence of Different Strength Training Protocol on Breaststroke Performance in Competitive Swimmers - Manalu, Nimrot; Fathynah SS, Syarifah; Panjaitan, Ivan Reano; Situmorang, Alifian Dwi Putra; Rivaldi, Deo; Tumanggor, Muhammad Farhan (INSPIREE: Indonesian Sport Innovation Review, 2025)
The  purpose  of  the study. This study aims to evaluate the effects of different strength training protocols on breaststroke performance in competitive swimmers, focusing on physiological adaptations, biomechanical efficiency, and performance outcomes. Materials and methods. A 24-week randomized controlled trial was conducted with 48 competitive breaststroke swimmers (26 male, 22 female, aged 18–25 years). Participants were assigned to three groups: traditional endurance training, high-intensity interval training (HIIT), and an integrated approach combining HIIT with technical refinement. Training intensity, volume, and technical components were systematically varied and monitored. Performance metrics, physiological adaptations, and biomechanical parameters were analyzed using mixed-effects linear models and Cohen’s d to determine effect sizes. Results. The integrated training group demonstrated the most significant improvements across all metrics. Performance times decreased by 2.3% (50m), 2.7% (100m), and 3.1% (200m) compared to smaller gains in the traditional and HIIT-only groups. Biomechanical efficiency improvements included increased stroke length (10.2%) and reduced drag coefficient (12.4%). Physiological enhancements, such as a 12.3% increase in lactate threshold speed and 8.5% improvement in VO₂max, were also observed. Conclusions. An integrated approach combining HIIT with technical skill development yields superior outcomes in breaststroke performance compared to traditional or HIIT-only protocols. This holistic training method optimizes both physiological and biomechanical adaptations, offering a robust framework for enhancing competitive breaststroke swimming.